Chimery i hybrydy. Podmiotowość prawna między dogmatem a konwencją: [Chimeras and hybrids. Legal subjecthood between dogma and convention] (Studia Prawnicze / The Legal Studies, 2015)
Aksjologia współczesnych zachodnich porządków prawnych opiera się na założeniach, które można określić mianem humanizmu prawniczego. Centralną kategorią jest w niej człowiek, którego prawom i dobru służyć ma państwo i prawodawstwo. Założenia takie znajdują wyraz w rozmaitych aktach prawnych – zarówno deklaracjach i konwencjach prawa międzynarodowego, jak i konstytucyjnych oraz ustawowych unormowaniach poszczególnych państw. Humanizm prawniczy w dużej części sięga metaprawnych założeń porządku prawnego stanowiących różnego rodzaju „oczywiste prawdy”, funkcjonujące na poziomie presupozycji tekstów prawnych i praktyki prawniczej. The developments of contemporary biotechnology involve production of creatures in which human and animal tissue or genetic information is mixed. Such creatures include biological chimeras, hybrids, cybrids or transgenic (humanized) animals. The paper describes the present state of the art of such research in order to examine its further conceptual implications for the account of personhood in law. I argue that there are already compelling reasons to overcome the radical, exceptionalist humanism as the foundation of the axiology of law. It should be transformed into the position that I call „modestly specist approach to personhood”. It abandons the specist idea of exclusive moral standing of human beings and opens for extending the scope of legal subjects beyond creatures not meeting the biological criteria of humanness. On the other hand, it rejects any decrease the present level of such protection offering the status of person to each human being from birth to death. Thus, it accepts applying different criteria to confer subjecthood and personhood on human and non-human (or partially human) creatures.